2022
DOI: 10.1186/s40550-022-00092-7
|View full text |Cite
|
Sign up to set email alerts
|

Fresh produce as a potential vehicle for transmission of Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a Gram-negative bacterium that has gained a stronghold inside healthcare settings. Due to the ability of A. baumannii to acquire antibiotic resistance easily, its presence in food products could pose a major threat to the public health. The aim of this study therefore, was to investigate the prevalence of A. baumannii in fresh produce and study their genetic diversity. A total of 234 samples of vegetables and fruits were collected. A. baumannii isolates were identified using CHROMaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Recently, one study reported that all isolates (n = 17) of Acinetobacter spp. derived from fresh vegetables and fruits were able to produce biofilms [26]. However, our results differ from the above findings, as a low frequency of isolates produced biofilms (13.3%).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Recently, one study reported that all isolates (n = 17) of Acinetobacter spp. derived from fresh vegetables and fruits were able to produce biofilms [26]. However, our results differ from the above findings, as a low frequency of isolates produced biofilms (13.3%).…”
Section: Discussioncontrasting
confidence: 99%
“…isolates by genetic sequencing of meat products [30]. A recent study detected four A. baumannii isolates from fresh fruits and vegetables (red apple, green grape, guava, and red radish) that were resistant to 16 antibiotics, including carbapenems, and were classified as extensively drugresistant (XDR) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A. baumannii , being an opportunistic nosocomial pathogen, gained advert importance due to its emerging multidrug-resistant characteristics caused by several virulence factors, including biofilm formation. It has been estimated that the formation of biofilm renders bacteria more resistant to antibiotics compared to other free-living cells [ 135 , 136 , 137 , 138 ]. The factors that initiate the formation of biofilm have been well-understood by the main interaction between the ambient environmental factors and the bacterial cells [ 138 , 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that the formation of biofilm renders bacteria more resistant to antibiotics compared to other free-living cells [ 135 , 136 , 137 , 138 ]. The factors that initiate the formation of biofilm have been well-understood by the main interaction between the ambient environmental factors and the bacterial cells [ 138 , 139 , 140 ]. In hospital surroundings, mainly in ICUs, A. baumannii currently exists as a potent drug-resistant bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prevalence of this pathogen in the community and outside hospitals remains unclear or poorly defined. A role of extra‐hospital reservoirs of A. baumannii in causing and spreading infections in the community has been suggested (Ababneh, Al‐Rousan, & Jaradat, 2022; Adjei et al, 2021; Al Atrouni, Hamze, et al, 2016; Anane et al, 2019; Berlau et al, 1999; Choi et al, 2012; Elbehiry et al, 2021; Eveillard et al, 2013; Rafei et al, 2015; Vangnai & Petchkroh, 2007). In addition, new strains of A. baumannii from the community could be introduced into the hospital environments by patients or their companions (Ababneh, Abulaila, & Jaradat, 2021; Al Atrouni, Hamze et al, 2016; Bocanegra‐Ibarias et al, 2015; de Azevedo et al, 2019; Ghaith et al, 2017; Grosso et al, 2011; Handal et al, 2017; Huang et al, 2016; Lorenzin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%